112k views
1 vote
X – 7y = –11
5x + 2y = -18

User Rokuto
by
4.2k points

1 Answer

4 votes

Answer:

hope this help you

Explanation:

Simplifying

X + -7y = -11

Solving

X + -7y = -11

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '7y' to each side of the equation.

X + -7y + 7y = -11 + 7y

Combine like terms: -7y + 7y = 0

X = -11 + 7y

Simplifying

X = -11 + 7y

------------------------------------------------------------------------------------------------------------

Solving

5x + 2y = -18

Solving for variable 'x'.

Add '-2y' to each side of the equation.

5x + 2y + -2y = -18 + -2y

Combine like terms: 2y + -2y = 0

5x = -18 + -2y

Divide each side by '5'.

x = -3.6 + -0.4y

Simplifying

x = -3.6 + -0.4y

User Ahmed Lahlou Mimi
by
4.7k points